2023
DOI: 10.1007/s40152-023-00296-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding change, complexities, and governability challenges in small-scale fisheries: a case study of Limbe, Cameroon, Central Africa

Abstract: Climate change, globalization, and increasing industrial and urban activities threaten the sustainability and viability of small-scale fisheries. How those affected can collectively mobilize their actions, share knowledge, and build their local adaptive capacity will shape how best they respond to these changes. This paper examines the changes experienced by small-scale fishing actors, social and governance complexities, and the sustainability challenges within the fisheries system in Limbe, Cameroon. Drawing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…These are youths still living with their parents, assisting their parents in fish harvesting activities, and/or operating/managing their parents' canoes. Previous research in these locales with fisheries actors identified their unwillingness to allow their children to engage in fisheries activities (Nyiawung et al, 2022(Nyiawung et al, , 2023.…”
Section: Survey and Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are youths still living with their parents, assisting their parents in fish harvesting activities, and/or operating/managing their parents' canoes. Previous research in these locales with fisheries actors identified their unwillingness to allow their children to engage in fisheries activities (Nyiawung et al, 2022(Nyiawung et al, , 2023.…”
Section: Survey and Sampling Methodsmentioning
confidence: 99%
“…These are youths still living with their parents, assisting their parents in fish harvesting activities, and/or operating/managing their parents’ canoes. Previous research in these locales with fisheries actors identified their unwillingness to allow their children to engage in fisheries activities (Nyiawung et al., 2022, 2023). To explore this problem, we used a structured questionnaire and a simple random sampling approach to survey approximately 70 youths from the six fishing communities.…”
Section: Methodsmentioning
confidence: 99%